Association Between Body Mass Index And Risk Of Symptomatic Cholelithiasis - Paudel, Madhav; Thapa, Bishal; Adhikari, Sanjit; Gyawali, Sagar; Singh, Deepak Raj (Journal of Society of Surgeons of Nepal, 2024)
Introduction: There is an increasing trend towards obesity worldwide and obesity is an important risk factor for various diseases. Gallstone disease is one of the most common and costly gastroenterological disorders. Although obesity is a risk factor for gallstone disease, the excess risk of symptoms associated with higher levels of obesity and weight change are poorly quantified. This study aims to find a relationship between BMI and symptomatic Cholelithiasis and to know the association between obesity and conversion to open cholecystectomy in the Nepalese population. Methods: This is a prospective observational study conducted in the Department of General Surgery Kathmandu Medical College from February 2019 to January 2020. Those patients who had indications for cholecystectomy were included in the study. Patient data were entered in a structured proforma. The collected data were stored in an electronic database (MS Excel Sheet). Statistical analysis was performed with statistical software (SPSS 23.0 for Windows). Results: A total of 337 patients were enrolled in the study. The mean age of the study population was 44.96±14 years. The maximum participants, 144(42.7%) had normal BMI (18.5-24.9kg/m2) and 65(19.2%) patients had BMI more than 30. The association between BMI and symptomatic cholelithiasis is was not significant(p=0.77). The majority of the participants had biliary colic i.e., 182(54%) followed by acute calculus cholecystitis in 67(19.9%), and pancreatitis in 44(13.1%). 31 cases were asymptomatic. The majority of the cases 325(96.4%) underwent laparoscopic cholecystectomy while 12(3.6%) of the cases underwent laparoscopic turned open cholecystectomy. Conclusion: The risk of development of symptomatic cholelithiasis as well as the risk of conversion to open cholecystectomy is not dependent on the BMI of the patients however both parameters have increased risk as age advances.